Analysis of e-learning system in the presence of social requirement - Fawareh, Hamed; Abu Alia, Abdulla (International Journal of Engineering and Technology, 2019)
Integration of the social network with e-learning systems is essential. Integration focuses more on a strategy that uses the benefits of social interactions and techniques in the development of e-learning systems. This approach cannot focus on finding the feature of e-learning components only, but will be useful and interactive solutions for e-learning organizations. This paper therefore seeks to propose a new social e - learning system model by integrating a social network into the e - learning system. The e-learning system incorporating social network systems is a significant advantage to increase user interaction and to measure not only the number of communications, but also the interaction meaning of the feature among users. In addition, we proposed the integration of the e-learning model in an educational organization with social and cultural learning. We proposed the integration of the e - learning model in an educational organization with social and cultural learning.Â
Keywords: CMS; E-Learning Systems; LMS; Social Network Systems.